Secretory leucoprotease inhibitor binds to NF-κB binding sites in monocytes and inhibits p65 binding - Taggart, Clifford C. (The Rockefeller University Press, 2005)
Secretory leucoprotease inhibitor (SLPI) is a nonglycosylated protein produced by epithelial cells. In addition to its antiprotease activity, SLPI has been shown to exhibit antiinflammatory properties, including down-regulation of tumor necrosis factor α expression by lipopolysaccharide (LPS) in macrophages and inhibition of nuclear factor (NF)-κB activation in a rat model of acute lung injury. We have previously shown that SLPI can inhibit LPS-induced NF-κB activation in monocytic cells by inhibiting degradation of IκBα without affecting the LPS-induced phosphorylation and ubiquitination of IκBα. Here, we present evidence to show that upon incubation with peripheral blood monocytes (PBMs) and the U937 monocytic cell line, SLPI enters the cells, becoming rapidly localized to the cytoplasm and nucleus, and affects NF-κB activation by binding directly to NF-κB binding sites in a site-specific manner. SLPI can also prevent p65 interaction with the NF-κB consensus region at concentrations commensurate with the physiological nuclear levels of SLPI and p65. We also demonstrate the presence of SLPI in nuclear fractions of PBMs and alveolar macrophages from individuals with cystic fibrosis and community-acquired pneumonia. Therefore, SLPI inhibition of NF-κB activation is mediated, in part, by competitive binding to the NF-κB consensus-binding site.